2002
DOI: 10.1590/s0034-77012002000200005
|View full text |Cite
|
Sign up to set email alerts
|

Política e questão de família

Abstract: Doutora pelo Museu Nacional -UFRJRESUMO: O problema abordado aqui consiste em entender porque e em que medida as brigas de família, as intrigas e questões na terminologia do sertão do Pajeú em Pernambuco, são também brigas políticas. Para abordá-lo, considerarei perspectivas exógenas e sobretudo nativas concernentes aos significados das brigas de famílias, menos com o propósito de afiliar-me a alguma delas do que de buscar vislumbrar as relações que trazem à tona. As interrogações em torno da natureza das luta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…This result reflects a cultural characteristic of Brazilian families: family members who live in close proximity generally participate very actively in each other's lives. An anthropologic study about families in Brazil showed that relationships are strongly centered on the family, and values such as unity and solidarity are widely emphasized (Marques, 2002), a characteristic that is seen even in the Brazilian television soap operas (Fadul, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This result reflects a cultural characteristic of Brazilian families: family members who live in close proximity generally participate very actively in each other's lives. An anthropologic study about families in Brazil showed that relationships are strongly centered on the family, and values such as unity and solidarity are widely emphasized (Marques, 2002), a characteristic that is seen even in the Brazilian television soap operas (Fadul, 2000).…”
Section: Resultsmentioning
confidence: 99%